A fast screening method for the detection of CERA in dried blood spots. Issue 5 (21st August 2021) - Rocca, Angela; Martin, Laurent; Kuuranne, Tiia; Ericsson, Magnus; Marchand, Alexandre; Leuenberger, Nicolas
Abstract: Continuous erythropoietin receptor activator (CERA) is a third‐generation erythropoiesis‐stimulating agent that was developed for the treatment of anemia. However, misuse of CERA for doping in endurance sports has been reported. Previous studies have shown blood as the matrix of choice for the detection of CERA, due to its high molecular weight. The use of dried blood spots (DBSs) for anti‐doping purposes constitutes a complementary approach to the standard urine and venous blood matrices and could facilitate sample collection and increase the number of blood samples available for analysis due to reduced costs of sample collection and transport. Here, we investigated whether CERA could be indirectly detected in extracts of single DBSs using an erythropoietin‐specific immunoassay that is capable of providing results within approximately 2 h. Reconstituted DBS samples were prepared from mixtures of red blood cell pellets and serum samples. The samples were collected in a previous clinical study in which six healthy volunteers were injected with a single, 200 μg dose of CERA. Using a commercially available ELISA kit, CERA was detected in the DBSs with a detection window of up to 20 days post‐injection. Furthermore, in order to demonstrate the fitness‐for‐purpose, three authentic doping control serum samples, which were identified as containing CERA, were analyzed by the presented methodological approach on DBS. The testing procedure described here could be used as a fast and cost‐effective method for the detection of CERA abuse in sport.